ANALYSIS OF SCIENCE LITERATION IN THE E-BOOK OF DISASTER EDUCATION IN SCIENCE LEARNING OF JUNIOR HIGH SCHOOL - Dita Puspita; Mudmainah Vitasari; Prasetyaningsih Prasetyaningsih (Jurnal Pembelajaran Sains, 2021)
This study aims to analyze the quality of scientific literacy in disaster education e-books in science learning in junior high schools. This research uses descriptive qualitative method. The research instrument used in this study was an observation. Based on the four categories of scientific literacy quality, the results of the analysis of the three disaster education e-books obtained from the percentage of the three e-books show that science as the body in minimizing disaster risk is 76.2%, science as a way to investigate in emergency response planning skills is 33.3%, science as a way of thinking in simulation activities was 66.7%, and the interaction between science, technology and the community in the socialization of alertness was 16.7%. Overall from the three e-books analyzed, that science as the body in minimizing disaster risk received the highest percentage and the interaction of science, technology with the community in the socialization of preparedness received a very low percentage. Therefore, it is necessary to pay attention so that scientific literacy is more balanced in the disaster education e-books used in science learning in order to provide a complete picture of science for students.